The effect of promoter methylation on MdMYB1 expression determines the level of anthocyanin accumulation in skins of two non-red apple cultivars - Changqing Ma; Chenjuan Jing; Bo Chang; Jiuying Yan; Bowen Liang; Li Liu; Yazhou Yang; Zhengyang Zhao (BMC Plant Biology, 2018)
Abstract Background Fruit color in apple (Malus domestica Borkh.) is ascribed mainly to the accumulation of anthocyanin pigments, and is an important trait for determining fruit market acceptance. Bagging is a commonly used treatment to enhance the red pigmentation in apple skin. The MdMYB1 transcription factor gene plays an important role in the biosynthesis of anthocyanin in apple after bag removal, but little is known about how MdMYB1 transcription is regulated. Results In this study, we investigated pigmentation in the non-red skinned cultivars ‘Granny Smith’ and ‘Golden Delicious’ after bag removal. The fruit skins of the two cultivars showed red/pink pigmentation after bag treatment. Transcript levels of MdMYB1, the master regulator of anthocyanin biosynthesis in apple, increased, and showed a correlation with anthocyanin content in both cultivars after bag removal. The MdMYB1 genomic sequences were compared in the two cultivars, which showed that the green-fruited cultivar ‘Granny Smith’ harbors the MdMYB1–1 and MdMYB1–2 alleles, while the yellow-fruited cultivar ‘Golden Delicious’ harbors only MdMYB1–2. A comparison of methylation levels in the 2 kb region upstream of the MdMYB1 ATG between the bag-treated fruits after removal from the bags and the unbagged fruits showed a correlation between hypomethylation and the red-skin phenotype in ‘Granny Smith’. Moreover, ‘Granny Smith’ fruits responded to treatment with 5-aza-2′-deoxycytidine, an inducer of DNA demethylation. An investigation of the MdMYB1 promoter in ‘Granny Smith’ showed reduced methylation in the regions − 2026 to − 1870 bp, − 1898 to − 1633 bp, and − 541 to − 435 bp after bag removal and 5-aza-2′-deoxycytidine treatments. Conclusions Differences in anthocyanin levels between ‘Granny Smith’ and ‘Golden Delicious’ can be explained by differential accumulation of MdMYB1-specific mRNA. Different levels of MdMYB1 transcripts in the two cultivars are associated with methylation levels in the promoter region. Hypomethylation of the MdMYB1 promoter is correlated with the formation of red pigmentation in ‘Granny Smith’ fruit skins. As a result, red pigmentation in Granny Smith’ was more intense than in ‘Golden Delicious’ fruits after bag removal.